The ghosts of Rose Hill - Romero, R. M. (Rachel Maria), 1987- (Peachtree Teen, 2022)
Staying with her aunt in Prague, aspiring violinist Ilana finds a forgotten Jewish cemetery where she meets a kindhearted ghost named Benjamin who introduces her to the enchanted side of the city where she resolves to save the boy she loves.